525 PROGNOSTIC RELEVANCE OF DEMOGRAPHIC FACTORS IN CARDIAC MAGNETIC RESONANCE-PROVEN ACUTE MYOCARDITIS. A COHORT STUDY. (15th December 2022) - Cannata, Antonio; Roy, Roman; Rios, Antonio Jordan; Ferone, Emma; Cassimon, Barbara; Sadler, Matthew; Rind, Irfan; Rosmini, Stefania; Piper, Susan; Giacca, Mauro; Mcdonagh, Theresa; Scott, Paul; et al.
Abstract: Aims: Acute myocarditis (AM) is a heterogeneous condition with variable estimates of survival. Contemporary criteria for the diagnosis of clinically suspected AM enable non-invasive assessment, resulting in greater sensitivity and more representative cohorts. We aimed to describe the demographic characteristics and long-term outcomes of patients with AM diagnosed using non-invasive criteria. Methods and Results: A total of 199 patients with cardiac magnetic resonance (CMR)-confirmed AM were included. The majority (n=130, 65%) were male and the average age was 39±16 years. Half of patients were White (n=99, 52%) with the remainder from Black and Minority Ethnic (BAME) groups. The most common clinical presentation was with chest pain (n=156, 78%), with smaller numbers presenting with breathlessness (n=25, 13%) and arrhythmias (n=18, 9%). Patients admitted with breathlessness were sicker and more often required inotropes, steroids, and renal replacement therapy (p<0.001, p<0.001, and p=0.01, respectively). Over a median follow-up of 53 (IQR 34–76) months, 11 patients (6%) experienced an adverse outcome, defined as a composite of all-cause mortality, resuscitated cardiac arrest, and appropriate implantable cardioverter defibrillator (ICD) therapy. Patients in the arrhythmia group had a worse prognosis, with a nearly 7-fold risk of adverse events (hazard ratio [HR] 6.97; 95% Confidence Interval [CI] 1.87–26.00, p=0.004). Sex and ethnicity were not significantly associated with the outcome. Conclusions: AM is highly heterogeneous with an overall favourable prognosis. Three quarters of patients with AM present with chest pain and this is associated with a benign prognosis. AM presenting with life-threatening arrhythmias is associated with higher risk of adverse events.